2002
DOI: 10.1038/sj.ejcn.1601289
|View full text |Cite
|
Sign up to set email alerts
|

The use of armspan measurement to assess the nutritional status of adults in four Ethiopian ethnic groups

Abstract: Objectives: To investigate the use of armspan as a proxy for height in the assessment of nutritional status using body mass index (BMI) for four ethnic groups in Ethiopia. Design: Cross-sectional study. Setting: Four regions in Ethiopia, namely Oromia, Amhara, Tigre and Somali Region. Subjects: A total of 1706 (884 males and 822 females) Ethiopians aged 18 -50 y from four different ethnic groups. Methods: Anthropometric measurements (weight, height and armspan) were obtained using standard techniques. BMI usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
43
1
3

Year Published

2003
2003
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(55 citation statements)
references
References 10 publications
6
43
1
3
Order By: Relevance
“…Longer mean height than arm span among Ellisras rural children was recorded in present study. Similar results were reported by Lucia et al (6) for the four ethnic groups Oromo, Ambara, Tigre and Somali in Ethiopia. Furthermore, Yabanci et al (10) reported shorter arm span compared with height among Turkish children aged 7-14 years.…”
Section: Discussionsupporting
confidence: 91%
“…Longer mean height than arm span among Ellisras rural children was recorded in present study. Similar results were reported by Lucia et al (6) for the four ethnic groups Oromo, Ambara, Tigre and Somali in Ethiopia. Furthermore, Yabanci et al (10) reported shorter arm span compared with height among Turkish children aged 7-14 years.…”
Section: Discussionsupporting
confidence: 91%
“…As it is already mentioned, all of them estimated body height from various anthropometric measurements, but it is important to emphasize that the arm span has been derived the most reliable body indicator for predicting body height of an individual (Mohanty et al; Ter Goon et al). However, it must be underlined that the individual and ethnic variations in respect of body height and its relation with arm span were already observed in European (Reeves et al) and African populations (de Lucia et al, 2002), while Mohanty et al (2001) have stated that the estimating equation varies from race to race, and ethnic group to ethnic group. In Steele and Chenier's study (1990), the arm span was nearly 8.3 cm more than the body height for black population (105.36% body height), whereas for white population this difference was only 3.3 cm (102.04% body height).…”
Section: Countrymentioning
confidence: 97%
“…7,18,29,45,[55][56][57][58][59][60][61][62][63][64][65][66][67] Findings have described how total arm span overestimates standing height. 7,18,29,45,[55][56][57][58][59][60][61][62][63][64][65][66][67] Before puberty, total arm span is closely correlated with standing height. After the onset of puberty (approximately 15 years), the correlation decreases and gender-related variations widen.…”
Section: Total Arm Spanmentioning
confidence: 99%